TINGKAT PEMBELAJARAN HOTS (HIGHER ORDER THINKING SKILLS) PADA MATERI SEPAK BOLA DALAM PENDIDIKAN JASMANI - Riki Rianto; Ahmad Atiq; Mimi Haetami (Universitas Tanjungpura, 2020)
AbstractThe problem discussed in this study is how the Learning Levels of HOTS (Higher Order Thinking Skills) in Soccer Material in Physical Education at LKIA Pontianak 2019. The purpose of this study is to determine the Learning Levels of HOTS (Higher Order Thinking Skills) in Soccer Material in Physical Education at LKIA Pontianak 2019. Descriptive research method involving two variables, namely the independent variable Personality and the dependent variable, namely the learning outcomes of physical education, sports and health. Population VII grade students of Pontianak LKIA Pontianak consisting of 6 classes, sampling using the random sampling method, researchers took one class of the total population, with a total sample of 54 students. This research technique uses data collection techniques with questionnaire or questionnaire. Data analysis using the percentage formula. The results of this study indicate the level of learning HOTS (Higher Order Thinking Skills) in the Soccer Material in Physical Education at LKIA Pontianak 2019 in the good category.Keywords: Learning HOTS, Soccer.